ACCOUNTING SYSTEM FOR PURCHASING RAW MATERIALS ON CREDIT AT PT. XYZ IN BEKASI - Titik Purwaningtyas Titik Purwaningtyas (ASIAN PUBLISHER, 2022)
ABSTRACT This final project research aims to determine the procedure for purchasing raw materials on credit, to determine the accounting records for purchasing raw materials on credit, and to determine the internal control of purchasing raw materials on credit at PT. Sanoh Indonesia in Bekasi. The research method used is a qualitative descriptive method, namely a method that aims to make a description or picture of the observations obtained and present them systematically. Based on the discussion it can be concluded that the Accounting System for Purchasing of Raw Materials on Credit at PT. Sanoh Indonesia still has several divisions that have concurrent duties, such as the warehouse section and the receiving department. The internal control system contained in PT. Sanoh Indonesia is still not in accordance with the internal controls contained in Mulyadi's book. Keywords: Accounting System, Credit Purchasing